RELATIONSHIP BETWEEN CARDIOVASCULAR RISK AND LUNG FUNCTION IN INDUSTRIAL SECTOR WORKERS (CIPEEX, 2025)
Introduction: Obesity is considered a pandemic disease as it has a high prevalence in both developed and developing countries and is associated with respiratory dysfunctions. The waist-to-hip ratio (WHR), in addition to being an indicator of obesity, is also considered a cardiovascular risk factor. Objective: To relate cardiovascular risk with pulmonary function in industrial sector workers. Methods: Analytical cross-sectional study involving workers from a construction materials industry. The sample consisted of 143 workers. The WC was calculated by dividing the waist circumference by the hip circumference, and respiratory function was measured by spirometry. The workers were stratified according to the WC (low and high risk). Results: 41 (28.7%) of the industry workers were at high risk, of which 25 were female. The age was higher in workers with high cardiovascular risk. The peak expiratory flow (PEF) ((∆=0.55 L/s, p
Keywords: Waist-to-hip ratio; cardiovascular risk; pulmonary function; industrial sector workers